Pengaruh Service Quality, Brand Image Terhadap Brand Loyalty Dengan Brand Trust Sebagai Mediasi - Sammy Natanael (Universitas Tarumanagara, 2019)
The purpose of this paper is to explore the direct and indirect influence of service quality and brand image on consumer’s brand loyalty with brand Trust as the mediation variable. Data were collected from 189 respondents and 187 responses had been used in this paper. “Service quality” measure used nine-item scale, “brand image” measured used six-item scale, “brand Trust” and “brand loyalty” measure used five-item scale. All measurement items were measured on five point Linkert-type scales. The four hypotheses in this paper have been tested. Service quality significantly gives positive influence to brand loyalty through brand Trust although service quality doesn’t significantly give positive influence to brand loyalty directly. Brand image significantly gives positive influences to brand loyalty directly and through the brand Trust. Brand Trust gives positive influences to brand loyalty.